1945
DOI: 10.1021/ja01219a027
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Constituents of Degras. A New Method of Structure Elucidation1

Abstract: The Acidic Constituents ok Dkukas 447 diffusion of which is slow compared with the rate of polymer chain growth.4. Employing a model based on this concept, it is calculated that gelation can only occur after these swollen molecules have filled 13-23% of the reaction mixture. Experimental results indicate 25-46% in fair agreement with calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1948
1948
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…These starter units are elongated by fatty acid synthases to the final iso-fatty acids (even numbered for isobutyryl-CoA; odd-numbered for isovaleryl-CoA) through extension with malonyl-CoA [2122]. Long-chain iso-fatty acids are important analytical reference compounds owing to the presence of these materials in tobacco [23], wool wax [24], butter fat [25], human sebaceous secretions [26] (adult skin [27], meibum [28], cerumen [29], and newborn vernix caseosa [3031]), and a wide variety of microbiological samples [1]. …”
Section: Introductionmentioning
confidence: 99%
“…These starter units are elongated by fatty acid synthases to the final iso-fatty acids (even numbered for isobutyryl-CoA; odd-numbered for isovaleryl-CoA) through extension with malonyl-CoA [2122]. Long-chain iso-fatty acids are important analytical reference compounds owing to the presence of these materials in tobacco [23], wool wax [24], butter fat [25], human sebaceous secretions [26] (adult skin [27], meibum [28], cerumen [29], and newborn vernix caseosa [3031]), and a wide variety of microbiological samples [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Tuberculostearic acid and its homologs, which have a methyl group substituted in the hydrocarbon chain, are found in Tubercule bacilli (6,7) and Microbispora cbromogenes M-22 (8). lso acids and anteiso fatty acids, which are substituted, respectively, on the next to last carbon and at the second from the last carbon, are obtained from a number of natural sources (9)(10)(11)(12)(13). Methylation of cellular lipid from the methyl group of methionine has been investigated in Agrobacterium turnefaciens (14), in Corynebacterium simplex grown on n-alkanes (15) and n-alkenes (16), and in Mycobacterium pblei (17).…”
Section: Introductionmentioning
confidence: 99%
“…Downing and Lindholm (1982) indicated that the majority of aliphatic components in cattle sebum are above C12, however, a C10 fatty acid component was reported. Both capric acid (0.3%) and stearic acid (0.2%) are present in wool wax of sheep (Weitkamp 1945), but it is not known if they are in cattle sebum.…”
Section: Skin Secretionsmentioning
confidence: 99%